2007
DOI: 10.1645/ge-852r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Helminth Fauna of Enyalius perditus (Reptilia: Leiosauridae): Relation to Host Age and Sex

Abstract: The purpose of this study was to determine how the gastrointestinal helminthofauna varies according to the age and sex of the lizard, Enyalius perditus, captured in Ibitipoca State Park in the state of Minas Gerais, Brazil, and to discuss the ecological and behavioral significance of these relationships. Fifty-five specimens of E. perditus were captured in drop traps, then killed, necropsied, and examined for the presence of helminths in the gastrointestinal tract. Nematodes, including Strongyluris oscari, Osw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Despite the wide distribution of Enyalius, few studies have addressed its helminth fauna and parasite ecology (Vicente et al, 1993;Durette-Desset et al, 2006;Sousa et al, 2007;Vrcibradic et al, 2007Vrcibradic et al, , 2008. Enyalius perditus…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wide distribution of Enyalius, few studies have addressed its helminth fauna and parasite ecology (Vicente et al, 1993;Durette-Desset et al, 2006;Sousa et al, 2007;Vrcibradic et al, 2007Vrcibradic et al, , 2008. Enyalius perditus…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide distribution of Enyalius, few studies have addressed its helminth fauna and parasite ecology (Vicente et al, 1993;Durette-Desset et al, 2006;Sousa et al, 2007;Vrcibradic et al, 2007Vrcibradic et al, , 2008. Enyalius perditus Jackson, 1978 is a small tropical lizard restricted to the easternmost Atlantic rainforest in southern and southeastern Brazil (Jackson, 1978;Lima & Sousa, 2006) that has been insufficiently studied with regard to many ecological and behavioural aspects (Lima & Sousa, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Host size and sex have a deep impact on diet and habitat preferences of lizards (Fitch, 1981), and this may also influence the patterns of prevalence and intensity of infection (Goater et al, 1987;Aho, 1990). Indeed, these correlations have been observed in a wide variety of Brazilian lizard species (Vrcibradic et al, 2000;Fontes et al, 2003;Anjos et al, 2005;Sousa et al, 2007). The lack of these correlations in B. lutzae may be due to our small sample size or host ecology, since differences of infection with age and sex are frequently linked with diet and habitat segregation (Van Sluys et al, 1994;Ribas et al, 1995, Anjos et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, recent studies have added to the knowledge of the helminth faunas of Enyalius spp. They include the description of three new nematode species of the genus Oswaldocruzia Travassos, 1917, each from a different species of Enyalius (Durette-Desset et al 2006), and surveys of the helminth assemblages of populations of E. bilineatus Duméril et Bibron, 1837 (Vrcibradic et al 2007) and E. perditus (Sousa et al 2007). In the present study we provide data on helminth species associated with two sympatric species of Enyalius, E. iheringii Boulenger, 1885 and E. perditus, from an Atlantic Rainforest area in Sno Paulo state, southeastern Brazil.…”
mentioning
confidence: 99%
“…Aho 1990, Sharpilo et al 2001, Bursey et al 2005a). Both Freitas (1955) and Sousa et al (2007) reported O. subauricularis from E. perditus, but Durette-Desset et al (2006) has shown that the species reported by Freitas (1955) was misidentified. This may also be the case for the study of Sousa et al (2007), as O. subauricularis is a parasite of frogs (Ben Slimane and Durette-Desset 1995).…”
mentioning
confidence: 99%